Combinational strategy for high-performance cancer chemotherapy. (July 2018) - Qin, Si-Yong; Cheng, Yin-Jia; Lei, Qi; Zhang, Ai-Qing; Zhang, Xian-Zheng
Abstract: The clinical outcomes of conventional mono-chemotherapy of cancers are usually far from satisfactory due to some issues such as tumor heterogeneity and resistance to chemotherapeutic drugs. With the increasing knowledge of molecular signal pathways and pathological mechanisms involved in the initiation and progression of cancers, collaborative strategies have been elaborated to optimize therapeutic outcomes. This review surveys the most recent advances in combination therapy including combination chemotherapy, chemotherapy plus gene therapy, chemotherapy plus phototherapy, as well as chemotherapy plus immunotherapy. Additionally, chemotherapy-involved multiple therapy that merges various therapeutic modalities is also presented. We try to elicit the rationales of applying these combinational formulations for cancer chemotherapy, which might provide new guidelines for high-performance cancer treatments. Graphical abstract: Combinational therapy, including combination chemotherapy, chemotherapy plus gene therapy, chemotherapy plus phototherapy, chemotherapy plus immunotherapy, as well as chemotherapy-involved multiple therapy, are confirmed to be the robust choices for high-performance cancer chemotherapy due to their abilities of conquering tumor heterogeneity and complexity, reversing multidrug resistance (MDR), and decreasing unwanted side effects, etc .